Pemberdayaan Masyarakat dan Keluarga melalui Pemberian Pendidikan Kesehatan dalam Merawat Anggota Keluarga dengan Gangguan Jiwa - Mila Triana Sari; Daryanto Daryanto (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2021)
Mental health is still a significant health problem in the world, including in Indonesia. The results of the 2018 Basic Health Research show the prevalence of severe mental disorders, such as schizophrenia, is 1.7 per 1000 population or around 400,000 people. This condition needs serious attention from all levels of cross-sectoral government both at the Central and Regional levels, as well as attention from the entire community, especially families. The lack of understanding of the community and families about how to treat People with Mental Ilness (PwMI) will have a non-optimal impact on the recovery of family members who suffer from mental disorders. The purpose of this community service is to increase the knowledge and ability of the community and family as an effort to achieve community and family independence in caring for (PWMI). The activities carried out were in the form of socialization, pre-test, health education using power points and leaflets, demonstration of how to care for (PWMI), post test and assistance to families of (PWMI). The activity was attended by village officials, health workers, community leaders, cadres and families with (PWMI). The result of this activity was an increase in the knowledge and ability of the community and family in caring for (PWMI) with a difference of 27.5% in the pre and post test scores. The conclusion is that providing health education to families and communities is effective in increasing knowledge and ability in caring for (PWMI), it is hoped that this service activity can provide information, knowledge and motivation to the community and families about how to care for (PWMI), so that it will encourage (PWMI) to live independently, productively, and confidently. in the community, free from stigma, discrimination or fear, shame and doubt also reduce the risk of recurrence in (PWMI).